Child sexual abuse: Listening to the victims - Ortiz-Tallo, Margarita; Calvo, Isabel (Archives of Community Medicine and Public Health, 2020)
Child Sexual Abuse (CSA) is a global public health concern. We present real testimonies of adults recalling their childhood, clinical reflections and scientific research data. Patients’ testimonies bring professionals closer to understanding their painful reality. All testimonies are from women who gave their consent to use their statement. Doctors and health professionals need to know this reality and be prepared to prevent and cope with abuse.